Pengaruh Pemberian Tugas Kelompok Terhadap Prestasi Belajar Mahasiswa Ilmu Pendidikan - Pakpahan, Damai Gaberia Br.; Bangun, Chamelia Tasri Br; Tambunan, Juwita Makaria; Nasution, Pauziah (CV. Eracita Grup, 2026)
A study group is a group of individuals who gather to share knowledge and discuss certain topics, usually with the same goals. This study aims to examine the effect of group assignments on the academic achievement of education students at Universitas Negeri Medan. The method used in this study is a quantitative approach by distributing questionnaires via Google Forms containing several statements related to study groups. The subjects were 28 students from the Faculty of Education, selected using purposive sampling, namely the selection of respondents based on criteria determined by the researcher. Data analysis was conducted using descriptive statistical analysis with the Jamovi application to provide an overview of data characteristics before inferential testing. The results show that the implementation of group work methods among students reached a very high category with an average actual score percentage of 87.4%, while learning motivation was also very high at 86.5%. Simple linear regression analysis produced the equation Y = 1.719 + 0.849X with a correlation coefficient of 0.878 (very strong), a coefficient of determination of 77%, and a significant t-test (Sig. = 0.000), indicating that the group work method has a positive and significant effect on learning motivation.